PKM Training Program on Productivity Improvement, Business Management, and Utilization of Social Media Platforms to Enhance Batik Kisenek Sales in the Mentawai Batik Artisan Community: PKM Pelatihan Peningkatan Produktivitas, Manajemen Usaha, dan Penggunaan Platform Media Sosial untuk Meningkatkan Penjualan Produk Batik Kisenek Komunitas Pembatik Mentawai - Muhammad Hendra; Safardi Safardi; Vilma Humaira; Saripah Haslinda; Afren Oktorialdo (The Future of Education Journal, 2025)
This Community Service Program (PKM) aims to improve productivity, business management, and digital marketing of the Kisenek Batik Community in Mentawai. The partners face problems such as limited production technology, absence of standard operating procedures (SOP), and lack of social media marketing skills. The methods used include socialization, training, technology implementation, mentoring, and evaluation. The results show an increase in partners’ skills in using production technology (batik stamping tools), preparing business SOPs, and optimizing social media platforms (Instagram, Facebook, TikTok) for product promotion. This program supports the achievement of the SDGs (No Poverty, Decent Work and Economic Growth), Asta Cita, and Key Performance Indicators of Higher Education.